Algodão branco e colorido cultivado no sistema orgânico com plantio direto em diferentes coberturas de solo - Arantes, Eurípedes Maximiano (2010)
Considered as alternative management more appropriate for tropical conditions, the no-tillage system can follow the principles of organic agriculture and contribute to the evolution and sustainability of organic cotton production systems. In order to generate usage information about soil covering plants for white and colored cotton fibers production in the organic system with no-tillage, an experiment was conducted in the farming years 2006/07 and 2007/08 in Cáceres-MT, with randomized block design, treatments disposed in scheme of split plots and four replicates. In the plots, were evaluated soil coverage consisting of crop residues of Estilozobium aterrimum, Cajanus cajan, Canavalia ensiformes, Crotalaria juncea, Pennisetum glaucum cv ADR 300, Sorghum bicolor cv BRS 307, mixture of species used, spontaneous vegetation and exposed soil. In the sub plots were evaluated upland cotton cultivars BRS ITAUBA (white) and CNPA AMT 19 (brown) in no-tillage on the crop residues of the soil covering plants cultivated in pre-planting. The plant coverage produces phytomass in sufficient quantities for adequate soil coverage. The Estilozobium aterrimum, in a general manner, shows greater extraction capacity and accumulation of nutrients, high lighting the potential cycling of nitrogen and phosphorus, while Pennisetum glaucum and Crotalaria show, respectively, greater potential cycling of potassium and magnesium. The crop residues of Canavalia ensiformes, spontaneous vegetation and Crotalaria provide low persistence coverage, while Pennisetum glaucum residues and Cajanus cajan provide more persistent coverage. During the process of residues decomposition, the nutrients following this descending order of release: K > P > N = S > Mg > Ca, being the potassium the nutrient with faster release and subject to losses. The Estilozobium aterrimum shows greater weed suppression capacity, showing potential for use in production system without application of herbicides, in contrast with the low suppression capacity of Pennisetum glaucum plants and spontaneous vegetation. The contribution of plant coverage residues promote on the surface layer of soil increases in values of attributes pH, MOS, P, K, Ca, Mg, V e CTC. The coverage does not influence the characteristics of fibers, but exerts significant effects on agronomic characteristics and productivity of cotton. The highest yield occurs in straws of Crotalaria juncea, Canavalia ensiformes, Estilozobium aterrimum and mixture of species. The cotton cultivars of brown fiber (CNPA AMT 19) shows productivity and quality of fiber lower than the cultivars of white fiber (BRS ITAÚBA), however has fibers with characteristics that meet the standards required by the textile industry.